2002
DOI: 10.1161/hs0202.103073
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Recanalization of Middle Cerebral Artery Occlusion During 2-MHz Transcranial Color-Coded Doppler Continuous Monitoring Without Thrombolytic Drug

Abstract: Background and Purpose— Experimental evidence indicates that ultrasound can accelerate thrombolysis. We report our findings on early recanalization during transcranial color-coded Doppler (TCCD) continuous monitoring in acute stroke patients with middle cerebral artery (MCA) main stem occlusion. Methods— We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 16 publications
4
61
0
1
Order By: Relevance
“…[32][33][34] On the other hand, 1 clinical study of the efficacy of sonothrombolysis in AMI found that TIMI grade 3 flow was achieved in only 64% of patients treated with both US and a fibrinolytic agent, 35 which is approximately the same rate previously reported for pharmacological thrombolysis without US. [5][6][7][8] The reason why clinical findings show US to be promising for potentiation of thrombolysis in stroke but not AMI is unclear at present.…”
Section: Discussionmentioning
confidence: 54%
“…[32][33][34] On the other hand, 1 clinical study of the efficacy of sonothrombolysis in AMI found that TIMI grade 3 flow was achieved in only 64% of patients treated with both US and a fibrinolytic agent, 35 which is approximately the same rate previously reported for pharmacological thrombolysis without US. [5][6][7][8] The reason why clinical findings show US to be promising for potentiation of thrombolysis in stroke but not AMI is unclear at present.…”
Section: Discussionmentioning
confidence: 54%
“…The CLOTBUST study (Alexandrov et al 2004b) evaluated the combined effect of rtPA administration within 3 h from symptom onset and TCD continuous monitoring at 2 MHz (diagnostic parameters), achieving a recanalization rate of 36% and an hemorrhagic transformation rate of 9%, not significantly different in comparison with the hemorrhagic rate of non-monitored patients. Other authors used TCCS for the same purposes with a diagnostic setting, with or without rtPA administration, confirming these findings (Cintas et al 2002;Eggers et al 2008). The data about ultrasound-enhanced thrombolysis has been recently analysed in a metaanalysis ) and the results were comforting, regarding the safety of sonothrombolysis with high frequency ultrasounds, with or without UCA.…”
Section: Ultrasound-assisted Thrombolysismentioning
confidence: 57%
“…14 Spontaneous recanalization is poorly documented in the literature and will depend on the selection of subjects studied and the timing of evaluation, as seen in the small number of published studies. 21,[24][25][26][27] However, the recanalization rate with medical therapy would have to be quite high to change the study results, and the highest rate of recanalization with medical therapy previously reported was 50%. 21 On the other hand, a lower recanalization rate with NIR treatment, below 67%, could render the intervention non-cost-effective.…”
Section: Discussionmentioning
confidence: 90%
“…Symptomatic ICH was not always reported in the literature and often was not specific for recanalization status. 15,[26][27][28] The Multi MERCI single-arm trial collected data on recanalization and ICH rates; however, the number of subjects in each group was small. The number of disabled survivors may be underestimated.…”
Section: Discussionmentioning
confidence: 99%